Nivel de cultura exportadora de los productores de camu camu de la región Loreto, Iquitos año 2023 - Rojas Melendez, Sara Marleni Geraldine (2023)
The objective of this research is to assess the level of export culture among camu camu producers in the Loreto region, Iquitos, during the year 2023. The study employs a quantitative and descriptive-explanatory approach, analyzing the dimensions, levels, and categories of the variable based on the population's opinions. The methodology is non-experimental and crosssectional, involving no deliberate manipulation of the variable and data collection taking place at a single point in time. Notably, 55.0% of the participants, equivalent to 22 individuals, consider the export culture to be "Low". In summary, it is concluded that the export culture among camu camu producers in the Loreto region, specifically in Iquitos in the year 2023, is assessed as "Low", supported by the assertion of 55% of the surveyed participants, thus validating the initially proposed hypothesis.